Wearable Multi-Sensor Gesture Recognition for Paralysis Patients - Thirumalai, T; Ramkumar, S; M, Selva kumar; ArunGanesh ME, K (International Journal of Computer Sciences and Engineering, 2019)
The parallelized person cannot establish the communication with the normal person. For this process implement the wearable glove. While the implementation of through wearable glove which helps to communicate with normal persons. The main objectives of this project are to detect the position of fingers and give command to control the home appliances. It consists of a glove in which flex sensor and accelerometer sensor are attached to an electronic conditioning circuit. The glove can have several other applications such as :( 1) The recognition of sign language, (2) To control the electrical parameters. These progressions focus on studying and implement a system for measuring the finger position of one hand. It can be used in rehabilitation intention and here we concentrate on biomedical application which exhibit coordination among parallelized patient and doctor. So this is a simple and moderate system.